Assessing of driving factors and change detection of mangrove forest in Kubu Raya District, Indonesia - Wiarta, Rinto; Firdaus Silamon, Rato; Ishag Arbab, Mohammed; Badshah, Muhammad Tariq; Hayat, Umer; Meng, Jinghui (Frontiers in Forests and Global Change, 2025)
Land cover change information is needed to support decision-making in land-based natural resource management, especially in coastal areas and mangrove ecosystems. This study aims to assess the drivers and detect mangrove forest cover change over the last 30 years in Kubu Raya District, Indonesia, using satellite imagery data from the United States Geological Survey (USGS) Earth Explorer. Maximum Likelihood Classification was used to analyze satellite images from four different recording years digitally: 1993 (Landsat 5), 2003 (Landsat 7), 2013 and 2023 (Landsat 8). Getis-Ord Gi* analysis was also used to observe fragmentation distribution patterns to determine areas with hot spots or cold spots with the Reticular Fragmentation Index (RFI) value as a consideration. Binary Logistic Regression (BLR) analysis was used to assess the drivers of social and natural variables, including population density, education, accessibility, soil type, rainfall, temperature, slope, and elevation. The results showed a significant decrease in mangrove forest cover, from 1,011.37 km2 in 1993–964.37 km2 in 2023, with an average loss of mangrove forest cover of 3.25 km2 per year, including mangroves, open areas, ponds, water bodies, agricultural areas, and settlements. The fragmentation pattern that occurs is that in some areas in the northern part, there are insignificant points in 1993 and then turn into hot spots in 2023. Meanwhile, from 1993 to 2023, there were cold spots that shifted and spread in the central part of the study area. In addition, social and natural variables provide values that are directly and inversely proportional to the driving factors. Social factors, especially population density, education, and land access, have a relationship with land change. Regulations made by the government and the presence of an educated community are the main points for mangrove ecosystem conservation; existing land access is not used as exploitation access but only for daily activities. Natural factors, such as alluvial soil types, have a high concentration of nutrients, making them ideal for sustainable agriculture and ponds. Rainfall intensity contributes to higher agricultural production and stable pond water. Conservation efforts must consider these changes and spatial dynamics to effectively protect mangrove ecosystems in the future.